Analysis of Broken Home Children Pictures at Salib Putih Orphanage Salatiga - Arindy Sabilla Dewi; Syakir Syakir; Eko sugiarto (Universitas Negeri Semarang, 2023)
This study discusses the visual expression of Broken Home children in the image of the pictures. For every individual, the family is referred to as a house that is always there in each of the individual conditions. However, it is not uncommon for the family to be a place to go home because of certain conditions experienced by an individual. This can be in the form of disharmony in the tang or broken home. The purpose of this study is to reveal whether the background factor of an individual can affect the work of the picture or not. This study uses a qualitative approach by applying the discipline of psychology and aesthetics. The research design is a case study, where data collection techniques use observations, interviews and document studies. For the validity of the data using the triangulation technique where this method is carried out by interview then followed by observation to obtain the same information. The study will be conducted at the Salib Putih Orphanage in Salatiga, with the research subject, the orphans who have a broken home background. The results revealed that a child's family background can affect the work of family -themed images. The child does not describe the state of his family in a bright manner. However, children tend to show their emotions and feelings honestly through the signs he made in his picture.